Behavioural variability and motor performance: Effect of practice specialization in front crawl swimming - Seifert, L.; De Jesus, K.; Komar, J.; Ribeiro, J.; Abraldes, J. A.; Figueiredo, P.; Vilas-Boas, J. P.; Fernandes, R. J. (Human Movement Science, 2016)
The aim was to examine behavioural variability within and between individuals, especially in a swimming task, to explore how swimmers with various specialty (competitive short distance swimming vs. triathlon) adapt to repetitive events of sub-maximal intensity, controlled in speed but of various distances. Five swimmers and five triathletes randomly performed three variants (with steps of 200, 300 and 400 m distances) of a front crawl incremental step test until exhaustion. Multi-camera system was used to collect and analyse eight kinematical and swimming efficiency parameters. Analysis of variance showed significant differences between swimmers and triathletes, with significant individual effect. Cluster analysis put these parameters together to investigate whether each individual used the same pattern(s) and one or several patterns to achieve the task goal. Results exhibited ten patterns for the whole population, with only two behavioural patterns shared between swimmers and triathletes. Swimmers tended to use higher hand velocity and index of coordination than triathletes. Mono-stability occurred in swimmers whatever the task constraint showing high stability, while triathletes revealed bi-stability because they switched to another pattern at mid-distance of the task. Finally, our analysis helped to explain and understand effect of specialty and more broadly individual adaptation to task constraint.